Principles For Teaching Uzbek Language In Educational Institutions (Czech Journal of Multidisciplinary Innovations, 2023)
This article raises the main problems in teaching the Uzbek language in Russianspeaking groups of educational institutions. Issues such as grammatical knowledge of the subject, the assuming of tasks for independent self-study, the use of terms related to text and specialization are highlighted.